Ecosystem Services Concept and Terminology as reflected in Shanghai Urban District Master Planning - Knöll, Verena; Falke, Matthias; Jing, Gan; Chen, Zheng; Dong, Nannan; Zepp, Harald (One ecosystem : ecology and sustainability data journal, 2025)
In the international scientific literature, ecosystem services (ES) and green infrastructure (GI) have rapidly emerged as promising frameworks for sustainable and resilient urban planning and development. At the science‒policy interface, a knowledge and implementation gap concerning ES and GI exists in many countries. In this paper, we analyse how the ES concept and GI principles are reflected in the narratives, which the Shanghai Master Plan tests to the Master Plans of all nine suburban Shanghai district Master Plans. Based on linguistic preprocessing, we systematically searched for the explicit and implicit references of ES and GI in the official documents. We found 802 relevant text passages and interpreted them according to their context-specific appearance. The analysis revealed that ES are not comprehensively integrated within the Shanghai Master Plan and the district Master Plans of Baoshan, Chongming, Fengxian, Jiading, Jinshan, Minhang, Pudong, Qingpu and Songjiang. The term ES was not explicitly used in any of the Master Plans. Instead, several terms were found that indicate conceptual similarity. By implicitly taking ES into account and prioritizing them, the districts' master plans reflect the characteristics of the natural landscape and land use patterns in their respective administrative areas. While ecological protection has been promoted and GI and ES are implicitly considered in Shanghai's master plans, a complete discursive shift towards a new ecological approach to urban planning, which is consistently based on GI and ES, has not yet been fully achieved in the master plans for all of Shanghai and the suburban districts.